2018
DOI: 10.24099/vet.arhiv.0031
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative traits of aged m. triceps brachii and m. gluteus biceps from lambs on supplemented feed

Abstract: The aim of this study was to evaluate the effect of the supplementation and aging in the gluteus biceps and triceps brachii muscles of lamb. Forty-eight Santa Inês lambs, with 15 kg average initial weight were slaughtered at 32 kg average final weight, after five months of supplementation. Twenty-four animals were allocated to sixteen pastures with residual leaf area index (2.6) and unsupplemented, the other twenty-four animals were allocated to the same conditions but were supplemented. The treatments were cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The iron(III)-catalyzed thiocyanation reaction was also investigated for the efficient synthesis of biaryl ether 12 , which is a key intermediate for the synthesis of toltrazuril ( 13 ), used to treat coccidiosis in livestock and poultry. 19 We proposed that an iron(III)-catalyzed thiocyanation could be used for a two-step synthesis of 12 from 2-methyl-4-nitro-1-phenoxybenzene ( 10 ) ( Scheme 3 ). Initial attempts at thiocyanation of 10 demonstrated that a 10 mol % catalyst loading of iron(III) chloride was required for good conversion.…”
Section: Resultsmentioning
confidence: 99%
“…The iron(III)-catalyzed thiocyanation reaction was also investigated for the efficient synthesis of biaryl ether 12 , which is a key intermediate for the synthesis of toltrazuril ( 13 ), used to treat coccidiosis in livestock and poultry. 19 We proposed that an iron(III)-catalyzed thiocyanation could be used for a two-step synthesis of 12 from 2-methyl-4-nitro-1-phenoxybenzene ( 10 ) ( Scheme 3 ). Initial attempts at thiocyanation of 10 demonstrated that a 10 mol % catalyst loading of iron(III) chloride was required for good conversion.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of protein-energy supplementation on carcass characteristics of sheep has also been verified. Nevertheless, despite favoring meat characteristics, this type of supplementation may increase lipid oxidation during the aging time and affect consumer acceptance ( 110 ). However, protein-mineral supplementation could improve the quantitative and qualitative carcass characteristics ( 120 ).…”
Section: Discussionmentioning
confidence: 99%
“… 2 Consequently, the trifluoromethanesulfenyl group is a valuable motif for agrochemical and pharmaceutical discovery. Several bioactive CF 3 S-containing compounds are commercially available and include toltrazuril ( 1 ), 3 used to treat coccidiosis in livestock and poultry, and the anorectic drug, tiflorex ( 2 ) ( Figure 1 ). 4 Trifluoromethanesulfenyl analogues of losartan (e.g., 3 ) have also been developed as potential hypotensive agents.…”
Section: Introductionmentioning
confidence: 99%